TEACHING LEARNING PROCESS OF READING SKILL AT ENGLISHDEPARTMENT OF MUHAMMADIYAH UNIVERSITY OF SURAKARTA: A MICRO ETNOGRAPHY - WATI, AYU PERMANA (2011)
This research aims at describing the teaching learning process on reading II at the second semester English Department of Muhammadiyah University of Surakarta. It is conducted to describe the learning objective, material, syllabus, the method of teaching reading, teacher role, learner role, classroom activity and the strenght and weaknessess the method used in teaching reading.In this research the data are derived from event, informant and document. There are three techniques in collecting the data namely: observation, interview and document. The researcher use the descriptive qualitative in analyzing the data. The data achieved from information related to the process of teaching learning process on Reading II, in form of field note, interview scripts and document. The result of the study are: 1) The learning objective is to back up the student's knowledge, ability and help the student's develop their reading in meaningful way. 2) The material, in teaching Reading II, the teacher used Reading Comprehension in 20 minutes by Learning Express New York. 3) The syllbus, Reading II the teacher not make syllabus but teacher used former syllabus. 4) The method used in teaching Reading II is active learning especially in information searching. 5) The roles of the teacher are as manager, as instructor, as facilitator, as evaluator, as counselor. 6) The roles of learner are as a listener and reader, and as a performer. 7) Classroom activity, in Reading II the classroom activity is working exercise. 8) The strengths of the method used are students active in the class, increase the vocabulary. The weaknesses are the teacher feels difficult to control the students in big class, there are many students are confused to understand the teacher's instruction and the teacher needs much time in the class.